EGRA AND EGMA INTERNATIONAL ASSESSMENT PROGRAMS AND TEACHING PRIMARY CLASS STUDENTS TO THINK INDEPENDENTLY THROUGH THEM - G.T.Baxronova (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract This article provides information about the EGRA and EGMA international assessment programs and how to teach primary school students to think independently.